The Penerapan E-Procurement Dan Pengendalian Internal Dalam Meningkatkan Efektivitas Pencegahan Fraud Pengadaan Barang Dan Jasa - Septiawan, Budi; Ningsih, Dini Fitria (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
Fraud is still a phenomenon in the activities of procurement of goods and services in various sectors, this study revealed how the implementation of e-procurement and adequate internal control will increase the effectiveness of fraud prevention of goods and services. The Bandung City Bhayangkara Hospital was the subject of this study. The sampling technique used is the saturation sample method which is part of non-probability. While the statistical analysis used in this study is the validity test, reliability test, multiple correlation analysis, multiple linear regression analysis, T test and F test. The results showed that the implementation of e-procurement on the effectiveness of fraud prevention procurement of goods and services is 32.8% . The influence of internal control on the effectiveness of fraud prevention procurement of goods and services is equal to 33%. Simultaneously shows that the magnitude of the effect of the implementation of e-procurement and internal control on the effectiveness of fraud prevention of goods and services procurement of 65.8%. Keywords : E-Procurement, Internal Control, Fraud Prevention of Goods and Services